INTEGRATION OF RESOURCE-BASED VIEW AND DIGITAL ECOSYSTEM CAPABILITY FOR SUSTAINABLE COMPETITIVE ADVANTAGE IN THE ERA OF ARTIFICIAL INTELLIGENCE: A STUDY ON PT KAWASAN INDUSTRI NUSANTARA (KINRA) - Asmaul Husna (CV. Radja Publika, 2025)
Special Economic Zones (SEZs) are important instruments for driving economic growth and industrialization, particularly in developing countries. The Sei Mangkei SEZ in Indonesia serves as a concrete example of the potential of SEZs in enhancing regional economic development. This study aims to determine how PT Kawasan Industri Nusantara (KINRA), as the manager of the Sei Mangkei SEZ, utilizes internal resources through a Resource-Based View (RBV) perspective, manages digital ecosystem capabilities, and leverages Artificial Intelligence (AI) capabilities to achieve Sustainable Competitive Advantage (SCA). A quantitative approach with a total sample of 125 employees was used, through a closed-ended questionnaire analyzed using PLS-SEM. The results show that RBV has a significant effect on SCA, emphasizing the importance of human resource competencies, technology, and infrastructure as the main foundation. Digital ecosystem capabilities have a positive, but insignificant, effect, indicating the need for stronger integration and collaboration between tenants, investors, and stakeholders. AI capabilities act as a moderating variable that strengthens the influence of RBV and digital ecosystem capabilities on SCA. These findings confirm that the integration of internal resources, the digital ecosystem, and AI technology can improve operational efficiency, innovation, market responsiveness, differentiation, and sustainable value creation in the Sei Mangkei Special Economic Zone (SEZ). This study recommends optimizing internal resources, strengthening the digital ecosystem, and strategically implementing AI for operational efficiency, industrial data management, and analytics-based decision-making. This integrative approach is expected to support the Sei Mangkei Special Economic Zone (SEZ) in maintaining long-term competitiveness, promoting inclusive growth, and creating sustainable economic value for the community and stakeholders.